The reflective urologist. (July 2021) - Terry, Tim; Bates, Anthon Simon
This paper reviews UK reflective practice in urology from historical and current usage perspectives. While appraisal, revalidation and annual review of competence progression processes mandate reflective practice its use in everyday urological practice is not evidenced in the urological literature. With the Covid-19 pandemic changes in urological care abound and front line NHS staff face being overwhelmed physically and emotionally by their experiences. Regular personal reflective practice and within teams offers vital support for urologists, their teams and their patients. A model for daily personal 'small' reflective practice and episodic 'big' reflective practice is proposed. Level of evidence: Not applicable.